2016
DOI: 10.1111/jvh.12582
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with poor adherence to antiviral treatment for hepatitis B

Abstract: Antiviral therapy for hepatitis B is effective and reduces the risk of progression to cirrhosis and liver cancer but is often required for an indefinite duration. Treatment adherence is important to prevent the development of resistance and optimize outcomes. Pharmacy adherence measures can be used to assess treatment adherence, with the medication possession ratio being less susceptible to bias than physician- or self-reported adherence. The aim of this study was to measure adherence in public hospital outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…Therefore, healthcare providers should actively inform patients about the importance of adhering to antiviral therapy and the potential consequences for skipping NUCs. One study based on a review of medical records of 69 immigrant patients in Chicago discovered that concerns about the long-term safety of NUCs was cited as one of the main barriers to treatment initiation and one of the main reasons for treatment discontinuation [26]. Likewise in our study, ‘Have experienced or worry about potential side effects’ was identified as the third most common barrier to NUC adherence.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, healthcare providers should actively inform patients about the importance of adhering to antiviral therapy and the potential consequences for skipping NUCs. One study based on a review of medical records of 69 immigrant patients in Chicago discovered that concerns about the long-term safety of NUCs was cited as one of the main barriers to treatment initiation and one of the main reasons for treatment discontinuation [26]. Likewise in our study, ‘Have experienced or worry about potential side effects’ was identified as the third most common barrier to NUC adherence.…”
Section: Discussionsupporting
confidence: 49%
“…From an initial screen of 878 titles, 30 studies providing data for 23,823 patients met our eligibility criteria and were taken through for review (Fig. ) . The majority (23 studies, 17,057 patients) were from high‐income settings, mainly the United States (seven studies), Australia (four studies), and France (three studies).…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review including 30 studies with different adherence measures estimated overall adherence to treatment in CHB with oral therapy was 75% and was similar in both high and low income settings [11]. Factors that have been shown to be related to poor adherence have included forgetting and change to routine, younger age, higher physician turnover and recent initiation of therapy [11][12][13][14][15]. Adverse reactions to medication can also result in poor adherence however antivirals for CHB have a low side effect profile and rarely adverse outcomes [16].…”
Section: Introductionmentioning
confidence: 99%